Generalized-Ensemble Algorithms for Protein Folding and Unfolding - Okamoto, Yuko (Current Physical Chemistry, 2012)
When one studies protein folding and unfolding by molecular simulations, one faces a great difficulty. Conventional simulations in the canonical ensemble are of little use, because they tend to get trapped in local-minimum-energy states, giving the results in error. A simulation in generalized ensemble performs a random walk in potential energy space and can overcome this difficulty. In this article we review some of powerful generalized-ensemble algorithms, namely, replica-exchange method, simulated tempering, and multicanonical algorithm, and their multidimensional/multivariable extensions.
Keywords: Multicanonical algorithm (MUCA)